Divine evil? the moral character of the God of Abraham - Bergmann, Michael 1964-; Murray, Michael James; Rea, Michael C. 1968- (Oxford Oxford University Press, 2010)
This title features 11 original essays by philosophers and biblical scholars addressing the character of God as portrayed in the Hebrew Bible. The book includes a critical commentary on each essay by another author, and replies to the critical comments by the original author
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; God -- Attributes; Das Böse; Gerechtigkeit; Opfer; Gewalt; Ethik; Gottesvorstellung; Aufsatzsammlung; Bible ; O.T ; Criticism, interpretation, etc; God ; Attributes; Aufsatzsammlung; Konferenzschrift -- 2009 -- Notre Dame, Ind